The Role of Leadership in the Talent Management and Employee Retention of Education in Abu Dhabi - Hammadi, Hasan Abdulla Al; Mohd Asri Bin Mohd Noor (European Journal of Multidisciplinary Studies, 2020)
The term Talent Management first emerged in 1998. The paper pointed to a major challenge facing large organizations in the U.S. at the time, which was the difficulty of attracting and retaining talented and experienced people especially for senior executive / leadership roles. The Talent Management as identified and mentioned by researchers. In general, these components could be considered as a component of talent retention and leadership, however, they do identify more with one of the main components than the other based on their characteristics Leadership: the talent mind set needs to be embedded throughout the organization, starting with the organization’s head (Kehinde 2012). This research is important for academic reason; it helps to provide essential data and enhance ability of the organization to employee retention to longer period. Data were collected by distributing questionnaires to 371 systematic randomly sampled respondents. Data collected were analyzed by using descriptive and inferential statistics. The research showed that The Role of Leadership in The Talent Management and Employee Retention of Education in Abu Dhabi.